Strategic effects of incomplete and renegotiation-proof contracts - Levent Koçkesen; Emanuele Gerratana (TÜSİAD-Koç University Economic Research Forum, 2009)
It is well known that non-renegotiable contracts with third parties may have an effect on the outcome of a strategic interaction and thus serve as a commitment device. We address this issue when contracts are renegotiable. More precisely, we analyze the equilibrium outcomes of twostage games with renegotiation-proof third-party contracts in relation to the equilibrium outcomes of the same game without contracts. We assume that one of the parties in the contractual relationship is unable to observe everything that happens in the game when played by the other party. This implies that contracts are incomplete and we show that such incompleteness restricts the set of equilibrium outcomes to a subset of Nash equilibrium outcomes of the game without contracts. Introducing renegotiation, in general, imposes further constraints and in some games implies that only subgame perfect equilibrium outcomes can be supported. However, there is a large class of games in which non-subgame perfect equilibriumoutcomes can also be supported, and hence, third-party contracts still have strategic implications even when they are renegotiable.
Keywords: C72; C78; D86; L13; 330; Third-Party Contracts; Strategic Delegation; Incomplete Contracts; Renegotiation; Unvollständiger Vertrag; Nash-Gleichgewicht; Nichtkooperatives Spiel; Theorie